Modeling and comparison of failure load with FEM and ANNs - Orcen, Gurbet; Bingol, Sedat; Gur, Mustafa (Sage Publications Ltd, 2016)
In this study, failure analysis was researched in woven glass fiber-reinforced epoxy resin composite plates jointed with two parallel pins under the effect of seawater. The effects of immersion time in seawater and changes in joint geometry on first failure loads were experimentally examined. In addition to this, the experimental results were compared with the results of the finite element analysis and artificial neural network modeling. The specimens were immersed in seawater for periods of 0, 3, and 6 months to observe the effects of seawater. For joint geometry, the parameters of the edge distance-to-upper hole diameter (E/D), the two hole-to-hole center diameter (K/D), the distance from the upper or the lower edge of the specimen to the center of the hole-to-hole diameter (M/D), and the width of the specimen-to-hole diameter (W/D) ratios were selected. In the numerical analysis, the finite elements models of the specimens were realized with the ANSYS 11.0 finite elements modeling and the Tsai-Wu failure criteria were used to predict the first failure loads. The comparison made in this study, results of the experimental, the finite element analysis, and artificial neural network modeling were compared and were found to be in good agreement for the first failure load.
Keywords: First failure load; failure analysis; seawater effects; pinned joint; composite plates; ANN modeling